The new construction products regulation (CPR) and the shift towards eco-efficient construction - Pacheco-Torgal, F. (2011)
On March 9th the European Union approved the Regulation (EU) 305/2011 related to the Construction Products Regulation (CPR) that will replace the current Directive 89/106/CEE already amended by Directive 1993/68/EEC known as the Construction Products Directive (CPD) beyond July 2013. The objective of the CPR is the same as the CPD, namely to “achieve the proper functioning of the internal market for construction products by means of harmonised technical specifications”. This paper analyses the main differences between CPD and CPR. This paper also addresses the new basic requirement of CPR “Sustainable use of natural resources” and the subject of hazardous substances in construction products.